PELATIHAN INSTALASI SERVER UJIAN BERBASIS KOMPUTER PADA SMK NEGERI 1 OGAN KOMERING ULU - Rifkie Primartha; M. Ihsan Jambak; Hadipurnawan Satria; Samsuryadi Sahmin (Annual Research Seminar (ARS), 2016)
One of the problems that might occurred when a school is going to hold Computer Based National Test (UNBK) is the inavailability of servers at the time of UNBK dissemination. During the dissemination process, everything is done only through simulation. This can cause problems, notably because the real world implementation could be significantly different than the simulation. SMK Negeri 1 Ogan Komering Ulu is one of the few high schools capable to hold UNBK aside of Paper Based Test. To intensify the preparation of UNBK, a Moodle system is installed on the school local server. It is expected to get the network administrators, students, and teachers ready for the future UNBK.